Pemanfaatan Aplikasi Digital untuk Peningkatan Tata Kelola Administrasi UMKM di Era Industri 5.0 - Wijaya, Acum; Sari, Deviana; Supriyanto, Supriyanto; Hasanan, Uwatul (Devotion: Journal Corner of Community Service, 2024)
This community service focuses on improving administrative management of MSMEs in Sebesi Island, Lampung Selatan, through the use of digital applications in the Industry 5.0 era. The subjects of this service include micro-entrepreneurs, fishermen, homestay managers, and local youth who are actively involved in economic activities. The main objectives are to enhance administrative efficiency, improve record-keeping accuracy, and strengthen the competitiveness of local businesses. The approach combines participatory methods, including socialization, workshops, focus group discussions, and hands-on mentoring to ensure active involvement and effective learning. The results indicate increased awareness and capability of digital administration, improved financial and inventory management, and expanded market access for local MSMEs. This program also fosters community collaboration and social capital, demonstrating that integrating technology with participatory empowerment can drive sustainable economic and social improvements.